Othonna cerarioides (Asteraceae: Othonnineae), a new species from Namaqualand, South Africa. (23rd March 2020) - Magoswana, Simon Luvo; Boatwright, James Stephen; Magee, Anthony R.; Manning, John C.
Abstract : Othonna cerarioides Magoswana and J.C. Manning is described as a new species from Namaqualand, Northern Cape Province of South Africa. It is an erect shrub with rod‐like stems and branches, bearing numerous spur‐shoots with obovate‐oblanceolate leaves clustered at the tips, and up to nine disciform capitula per spur‐shoot. Othonna cerarioides is anomalous in the genus in that the style of some of the disc florets is bifid. Othonna is diagnosed within subtribe Othonnineae by female‐sterile disc florets with simple (or very rarely minutely bifid) styles. The disc florets in the closely related genus Hertia are bisexual with well branched styles.